Enhancement of the electrochemical performance of LiCoPO4 by Fe doping. Issue 22 (15th November 2021) - Aboraia, Abdelaziz M.; Moustafa, M.G.; Shapovalov, Viktor V.; Guda, Alexander A.; Elmasry, F.; Soldatov, Alexander
Abstract: LiCoPO4 is an attractive cathode material, but it undergoes poor electronic conductivity and electrochemical performance. This performance is enhanced by substituting iron antisite Cobalt to reduce the direct interaction between the cathode and the electrolyte. Thus, LiCoPO4 doped with Fe was synthesized by the microwave-assisted solvothermal route at 220 °C. According to X-ray diffraction analysis, a single orthorhombic Pn21a phase (a = 10.02 Å, b = 6.71 Å and c = 4.96 Å) was obtained, which transited to Pnma phase (a = 10.21 Å b = 5.92 Å and c = 4.76 Å) after annealing at 700 °C in air. The morphology and particle size of the sample changed after annealing, as shown by TEM. The electrochemical cycling of an annealed sample showed the initial discharge capacity of 125mAh g −1 compared to 12 mAh g −1 for the non-annealed sample, which can be regarded as a partial coating by FePO4 as obtained from X-ray absorption spectroscopy analysis.